### What is the sum of the first ^@ n ^@ terms of the geometric series ^@ 1, \dfrac{ 3 }{ 5 }, \dfrac{ 9 }{ 25 } \space ...? ^@

**Answer:**

^@ \dfrac{ 5 }{ 2 } \left[ 1 - \left( \dfrac{ 3 }{ 5 } \right)^n \right] ^@

**Step by Step Explanation:**

- The sum of first ^@ n ^@ terms of a ^@ G.P. ^@ is given by,

^@ S_n = \dfrac{ a(1 - r^n) }{ (1 - r) } ^@

Here, the first term, ^@a = 1^@ and

the common ratio, ^@ r = \dfrac{ a_{k+1} }{ a_k } \text{ where } k ≥ 1

^@

^@ \implies r = \dfrac{ \dfrac{ 3 }{ 5 } } { 1 } = \dfrac{ 3 }{ 5 } ^@ - The sum of first ^@ n ^@ terms of this ^@ G.P. ^@ is given by,

@^ \begin{align} S_n &= \dfrac { (1)\left(1 - \left( \dfrac{ 3 }{ 5 } \right)^n \right) } { 1 - \dfrac{ 3 }{ 5 } } \\ &= \dfrac { \left(1 - \left( \dfrac{ 3 }{ 5 } \right)^n \right) } { \dfrac{ 2 }{ 5 } } \\ &= \dfrac{ 5 }{ 2 } \left[ 1 - \left( \dfrac{ 3 }{ 5 } \right)^n \right] \\ \end{align} @^ - Hence, the sum of the first ^@ n ^@ terms of the ^@G.P.^@ is ^@ \dfrac{ 5 }{ 2 } \left[ 1 - \left( \dfrac{ 3 }{ 5 } \right)^n \right] ^@.